2018
DOI: 10.3892/etm.2018.6781
|View full text |Cite
|
Sign up to set email alerts
|

Axon guidance pathway genes are associated with schizophrenia risk

Abstract: In the present study, we analyzed schizophrenia (SCZ)-related genome-wide association studies (GWAS) to identify genes and pathways associated with SCZ. We identified 1,098 common genes (1,098/9,468) and 20 shared KEGG pathways (both P<0.01) by integrating candidate genes from the European and American SCZ-related GWAS. The pathways related to axon guidance, long term potentiation and arrhythmogenic right ventricular cardiomyopathy (ARVC) were highly significant (P<10−3). Moreover, 15 axon guidance pathway-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 42 publications
1
26
0
1
Order By: Relevance
“…Transcriptomic analysis of these cortical neuroids also identified AP-specific dysregulation of pathways involved in multiple aspects of neurodevelopmental signaling, including axonal guidance, integrins and gap junctions, Wnt signaling, and GABA receptor function, with most genes in these pathways exhibiting reduced expression in the AP relative to controls. Accumulating evidence from both imaging and high content genomic studies of post-mortem brain has identified aberrations in axonal growth and correspondingly disrupted expression of genes that mediate axonal growth in ASD and in other psychiatric disorders, including altered expression of Slit, Robo, Ephrin, and Semaphorin family genes (45,51,52). Here, the AP model exhibited altered expression of multiple axonal guidance molecules (SLIT2, EPHA8, EPHA5, EPHB4, and ROBO2).…”
Section: Discussionmentioning
confidence: 87%
“…Transcriptomic analysis of these cortical neuroids also identified AP-specific dysregulation of pathways involved in multiple aspects of neurodevelopmental signaling, including axonal guidance, integrins and gap junctions, Wnt signaling, and GABA receptor function, with most genes in these pathways exhibiting reduced expression in the AP relative to controls. Accumulating evidence from both imaging and high content genomic studies of post-mortem brain has identified aberrations in axonal growth and correspondingly disrupted expression of genes that mediate axonal growth in ASD and in other psychiatric disorders, including altered expression of Slit, Robo, Ephrin, and Semaphorin family genes (45,51,52). Here, the AP model exhibited altered expression of multiple axonal guidance molecules (SLIT2, EPHA8, EPHA5, EPHB4, and ROBO2).…”
Section: Discussionmentioning
confidence: 87%
“…Clinically, this is consistent with the general consensus that SCZ is strictly neuropsychiatric as opposed to degenerative. In this same vein, axonogenesis (p_microglia<2.91e-5, p_oligodencrocytes<4.56e-12, p_excitatory<5.27e-17, p_inhibitory<7.91e-16) [68], regulation of cell morphogenesis (p_microglia<1.01e-8, p_oligodencrocytes<9.11e-10, p_excitatory<1.56e-8, p_inhibitory<2.65e-9) [69], neuronal cell synapses (p_oligodencrocytes<7.26e-11, p_excitatory<2.28e-25, p_inhibitory<2.17e-26) [49] were all enriched. Multiple axon guidance pathways associated with general axon growth in axonogenesis have been heavily implicated in the broad mechanism of SCZ pathology; elucidating this mechanism has remained difficult in part due to the polygenic nature of the disease.…”
Section: Revealing Disease Related Functions Involving Multiple Cell-mentioning
confidence: 89%
“…Multiple axon guidance pathways associated with general axon growth in axonogenesis have been heavily implicated in the broad mechanism of SCZ pathology; elucidating this mechanism has remained difficult in part due to the polygenic nature of the disease. Broadly, it is thought that missteps in guidance cues can lead to eventual presentation and disease onset, but the underlying pathway remains unclear [68]. On the front of cell morphogenesis, early life neurodevelopmental genetic markers may suggest causal links with alterations in hippocampal cell differentiation points leading to cascades of downstream effects [69].…”
Section: Revealing Disease Related Functions Involving Multiple Cell-mentioning
confidence: 99%
“…Finally, on chromosome 18, DCC (the most significant hit) encodes a netrin 1 receptor with a role in axon guidance, and has been previously reported to be associated with anhedonic phenotypes in mice and humans 62 and potentially with schizophrenia pathogenesis 63 . We have previously identified DCC in GWAS of mood instability 64 , suicidality 65 and multisite chronic pain 66 .…”
Section: Genes Within Anhedonia-associated Locimentioning
confidence: 99%